Adherence in pediatric renal recipients and its effect on graft outcome, a single‐center, retrospective study. (23rd November 2020) - Feddersen, Nele; Pape, Lars; Beneke, Jan; Brand, Korbinian; Prüfe, Jenny
Abstract: Background: In recent years, treatment‐adherence gained increasing attention in nearly every area of medicine including transplant medicine. Medication adherence following solid organ transplantation is known to be indispensable for a satisfactory allograft survival. Methods: We examined 60 patients between the ages of four months and 20 years who underwent kidney transplantation at Hannover Medical School between January 2011 and August 2017. Age at transplantation varied from 4 months to 20 years. 12 patients (20%) already underwent their second solid organ transplantation. 5 patients (8.3%) had a combined kidney‐liver‐transplantation. We used two different methods for rating adherence: An objective one based on the coefficient of variation (CoV%) of immunosuppressant trough levels, and a subjective questionnaire answered by the patients themselves, their parents or legal custodians, the treating pediatrician, as well as by the attending psychologist. Results: The CoV% in our study was by‐trend higher in those patients who suffered from a biopsy‐proven rejection (x̅CoV% = 35.7, σ CoV% = 30.1 in patients with rejection vs. x̅ CoV% = 26.0, σ CoV% = 10.5 in patients without rejection). Furthermore, the psychologist's assessment correlated significantly both with rejections as well as with the formation of de novo donor‐specific antibodies (dnDSA) while the pediatrician's rating showed no correlation (Prejections = 0.005 and PdnDSA = 0.03 for psychologist's rating vs. Prejections = 0.50 and PdnDSA = 0.50 for pediatrician). Conclusions: Apart from underlining the importance of medication adherence, the present research stresses the role of a multi‐disciplinary treatment approach to support pediatric renal transplant recipients and their families.